Development of cell labeling and gene editing tools in urochordate Ciona - Xiang Li; Lu Mu; Hongzhe Peng; Sun Nyunt Wai; Longjun Pu; Bo Dong (Marine Life Science & Technology, 2025)
Urochordate Ciona spp. are ideal marine model organisms for studying embryogenesis and developmental and evolutionary biology. However, the effective implementation of genetic labeling and CRISPR/Cas9-based editing tools at cellular resolution remains challenging. This study successfully developed and validated a collection of Gateway-based vectors for cell labeling in Ciona spp. The destination vector sets contained two Gateway cassettes flanked by Minos sites, allowing the N- or C-terminal tagging of a protein of interest with various fluorescent markers. In addition, we optimized the CRISPR/Cas9 and CRISPR/dCas9 systems by incorporating P2A-mCherry, a fluorescent indicator for Cas9 expression at cellular resolution. We demonstrated the effective destruction or inhibition of target genes when CRISPR constructs were introduced into fertilized eggs. Furthermore, we engineered a dual fluorescence sensor system that helps visualize successful gene knockouts at the cellular level in specific tissues. The genetic tools developed in this study offer a robust method for gene expression, cell tracking, and subcellular protein localization while also facilitating tissue-specific functional analysis in Ciona embryos and other model systems.

Experimental investigation on the behavior of cyclic-laterally loaded lattice-shaped diaphragm wall in soft soil - Jiujiang Wu; Haodong Hu; Yang Zhang; Longjun Pu; Jin Yin (Ocean Engineering, 2024)

Integrative analysis of transcriptomic profile reveals potential roles of miRNAs in regulating development of Marsupenaeus japonicas - Jing Wang; Longjun Pu; Xiaojuan Zhang; Cuicui Liang; Dandan Dong; Jiantao Guan; Huarong Guo (Journal of Oceanology and Limnology, 2024)

Computational identification and characterization of microRNAs and their targets in Penaeus monodon - Longjun Pu; Jing Wang; Yu Wang; Jianwei Zuo; Huarong Guo (Journal of Oceanology and Limnology, 2018)